INOVASI PENGELOLAAN KELAS INDUSTRI PADA PROGRAM PINTAR BERSAMA DAIHATSU DI SEKOLAH MENENGAH KEJURUAN - Hartanto Hartanto; Manap Somantri (Manajer Pendididikan, 2022)
The focus of learning in SMK needs to emphasize the mastery of the skills, knowledge, attitudes and values ​​needed by the industry. The purpose of this study is to describe industrial-class management innovation (Planning, Implementation and Evaluation) in the Daihatsu Smart Joint Program (PPBD) in Vocational High Schools. This research method uses a qualitative approach with a descriptive type of research based on the philosophy of postpositivism, to examine the condition of natural objects. The research object is Vocational School Negeri 4 Kepahiang in the Industrial-class Automotive Light Vehicle Engineering Program Smart Program with Daihatsu. The research results obtained that the management of the industrial class begins with planning to collaborate between the school and the industry and continues with collaboration in the preparation of an industrial class curriculum between the SMK curriculum and industrial qualifications. Implementation management is adjusted to the curriculum that has been prepared with partner industries. The management of the industrial class program evaluation is carried out after the process of implementing the industrial class by both parties.